MACRO ECONOMICS FACTORS AND BANK LENDING BEHAVIOUR IN INDONESIA - Rofikoh Rokhim; Yinylia Rusli (Economic Journal of Emerging Markets, 2012)
AbstractThis study examines the influencing macro economics factor in lending distribution and observes the comparison of each factor based on lending type which are investment, working capital and domestic consumption lending. Using data of Indonesian commercial banks between 2003-2011 and a balanced panel method, it finds that bank liquidity and inflation rate have significant negative effect, while number of banks has strong positive influence to stimulate lending distribution. Moreover, saving rate and GDP growth were found not meaningfully contributed to change investment lending distribution, but they significantly influenced the other lending distribution. Lastly, reserve requirement and exchange rate did not significantly influence all lending type.Keywords: Loan, interest rate, growth, GDP.JEL Classification Numbers: G21, E43, E51AbstrakStudi ini meneliti faktor ekonomi makro yang mempengaruhi distribusi pinjaman dan mengamati perbandingan masing-masing faktor berdasarkan jenis pinjaman yaitu pinjaman investasi, modal kerja dan konsumsi. Dengan menggunakan data dari bank-bank komersial di Indonesia antara 2003-2011, dengan menggunakan analisis data panel, ditemukan bahwa likuiditas perbankan dan tingkat inflasi berpengaruh negatif signifikan, sedangkan jumlah bank berpengaruh positif dan kuat untuk mendorong distribusi pinjaman pada semua jenis pinjaman. Selain itu, tingkat tabungan dan pertumbuhan PDB ditemukan tidak bermakna dalam kontribusinya untuk mempengaruhi distribusi kredit investasi, tetapi secara signifikan mempengaruhi distribusi pinjaman lainnya. Terakhir, GWM dan nilai tukar tidak signifikan mempengaruhi semua tiga kategori jenis pinjaman. Keywords: Loan, interest rate, growth, GDPJEL Classification Numbers: G21, E43, E51